1993
DOI: 10.1037/0021-843x.102.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Relation of parental alcoholism to early adolescent substance use: A test of three mediating mechanisms.

Abstract: The current study assessed 3 hypothesized mediating mechanisms underlying the relation between parental alcoholism and adolescent substance use. Using structural equation modeling, we analyzed data obtained from a large community sample of adolescent children of alcoholics and a demographically matched comparison group. Results suggested that parental alcoholism influenced adolescent substance use through stress and negative affect pathways, through decreased parental monitoring, and through increased temperam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
393
7
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 414 publications
(436 citation statements)
references
References 61 publications
28
393
7
2
Order By: Relevance
“…An additional item taken from the same scale ("parents punish me if I do something I'm not supposed to"; Metsapelto and Pulkkinen, 2003) was combined with a single item from the home atmosphere scale ("strict"), resulting in a smaller and, therefore less reliable, two-item scale of perceived parental discipline (α = .52). Last, three items (α = .73), rated on a 4-point scale from almost always to almost never, were used to assess parental knowledge ("parents know my daily program," "parents know my interests, activities, whereabouts," and "parents know where I am and who I am with when not at home"; Chassin et al, 1993). Accordingly, the present study assesses a relatively comprehensive set of diverse, but related, dimensions of parenting, especially for such a large, population-based epidemiological sample.…”
Section: Methodsmentioning
confidence: 99%
“…An additional item taken from the same scale ("parents punish me if I do something I'm not supposed to"; Metsapelto and Pulkkinen, 2003) was combined with a single item from the home atmosphere scale ("strict"), resulting in a smaller and, therefore less reliable, two-item scale of perceived parental discipline (α = .52). Last, three items (α = .73), rated on a 4-point scale from almost always to almost never, were used to assess parental knowledge ("parents know my daily program," "parents know my interests, activities, whereabouts," and "parents know where I am and who I am with when not at home"; Chassin et al, 1993). Accordingly, the present study assesses a relatively comprehensive set of diverse, but related, dimensions of parenting, especially for such a large, population-based epidemiological sample.…”
Section: Methodsmentioning
confidence: 99%
“…Research on general parenting among individuals with an AUD demonstrates that alcoholic parents engage in suboptimal parenting (see Zahn-Waxler et al, 2002, for a review). In addition, maladaptive general parenting represents a mechanism of the intergenerational transmission of AUD (e.g., Chassin et al, 1993). Although not as widely studied, there is also evidence that parents' drinking may affect alcohol-specifi c parenting.…”
Section: Parental Alcohol Use Disorder and Alcohol-specifi C Parentingmentioning
confidence: 99%
“…Numerous studies have reported links between substance abuse/dependence, stress, anxiety, depression, anger and other affective symptoms (e.g., Cappell & Grealey, 1987;Chassin, Pillow, Curran, Molina & Barrera, 1993). Drug addicts typically experience more anxiety, irritability, moodiness, anger and egocentricity than non-addicts (Francis, 1996), and individuals with high neuroticism scores tend to exhibit heavier alcohol use than people with low scores (Prescott, Neale, Corey & Kendler, 1997;Rankin, Stockwell & Hodgson, 1982;Sieber & Angst, 1990).…”
Section: Nmr Expectanciesmentioning
confidence: 99%